Effect of Sodium Fluoride on Bone Biomechanical and Histomorphometric Parameters and on Insulin Signaling and Insulin Sensitivity in Ovariectomized Rats - de Cássia Alves Nunes, Rita [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Pereira, Amanda Gomes [UNESP]; Pereira, Renato Felipe [UNESP]; de Lima Coutinho Mattera, Maria Sara [UNESP]; Ervolino, Edilson [UNESP]; Louzada, Mário Jefferson Quirino [UNESP]; Buzalaf, Marília Afonso Rabelo; Silva, Cristina Antoniali [UNESP]; Sumida, Doris Hissako [UNESP] (Springer Nature, 2016)
Osteoporosis is a systemic disease characterized by bone degradation and decreased bone mass that promotes increased bone fragility and eventual fracture risk. Studies have investigated the use of sodium fluoride (NaF) for the treatment of osteoporosis. However, fluoride can alter glucose homeostasis. The aim of this study was to evaluate the effects of NaF intake (50 mg/L) from water on the following parameters of ovariectomized (OVX) rats: (1) tyrosine phosphorylation status of insulin receptor substrate (pp185 (IRS-1/IRS-2)) in white adipose tissue; (2) insulin sensitivity; (3) plasma concentrations of glucose, insulin, total cholesterol, triglyceride, TNF-α, IL-6, osteocalcin, calcium, and fluoride; (4) bone density and biomechanical properties in the tibia; and (5) tibia histomorphometric analysis. Fifty-two Wistar rats (2 months old) were ovariectomized and distributed into two groups: control group (OVX-C) and NaF group (OVX-F), which was subjected to treatment with NaF (50 mg/L) administered in drinking water for 42 days. The chronic treatment with NaF promoted (1) a decrease in pp185 (IRS-1/IRS-2) tyrosine phosphorylation status after insulin infusion in white adipose tissue and in insulin sensitivity; (2) an increase in the plasma concentration of insulin, fluoride, osteocalcin, calcium, triglyceride, VLDL-cholesterol, TNF-α, and IL-6; (3) a reduction in the trabecular width, bone area, stiffness, maximum strength, and tenacity; (4) no changes in body weight, food and water intake, plasma glucose, total cholesterol, HDL-cholesterol, LDL-cholesterol, bone mineral content, and bone mineral density. It was concluded that chronic treatment with NaF (50 mg/L) in OVX rats causes a decrease in insulin sensitivity, insulin signaling transduction, and biochemical, biomechanical, and histomorphometric bone parameters.
Keywords: Bone density; Fluoride; Insulin resistance; Osteoporosis; Rats